Selection of optimum sustainable biofuel for maritime transportation using analytic hierarchy process - Sevim, Cagatayhan; Zincir, Burak (TAYLOR & FRANCIS LTD, 2026)
The increase in emissions from ships has prompted the International Maritime Organisation to take action and new emission regulations have been put into effect. Using low-carbon alternative fuels is a key part of the International Maritime Organisation's strategy plan. Biofuels have significant potential in the maritime industry's transition to alternative fuels due to their characteristic features. The aim of this study is to identify, through a scientific comparison, the most suitable biofuel that is sustainable for maritime transportation. The comparison was made with 7 criteria using the Analytic Hierarchy Process methodology. Since a life cycle assessment approach was adopted in the comparison, well-to-wake emission performance and indirect land use change factor were also included within the criteria. For calculating the weights of the criteria, a questionnaire was created and 15 experts were consulted. For determining the performance of biofuel alternatives on the criteria, information from the literature was utilised. Experts identified safety as the most crucial criterion, followed by well-to-wake emissions and compatibility. The results indicate that biofuels like Fischer-Tropsch diesel and 3rd generation Hydrotreated vegetable oil, which excel in safety, well-to-wake emissions, and compatibility, are optimum biofuels for the shipping industry's transition to low-carbon fuels.Abbreviations: AHP: Analytic Hierarchy Process; ASTM: American Society for Testing and Materials; CI: Consistency Index; CO: Carbon Monoxide; CO2: Carbon Dioxide; CR: Consistency Ratio; DME: Dimethyl Ether; FAME: Fatty Acid Methyl Ester; FT-Diesel: Fischer-Tropsch Diesel; GHG: Greenhouse Gas; GJ: Gigajoule; GLERL: Great Lakes Environmental Research Laboratory; H2: Hydrogen; HC: Hydro Carbon; HFO: Heavy Fuel Oil; HTL: Hydrothermal Liquefaction; HVO: Hydrotreated Vegetable Oil; IEA: International Energy Agency; ILUC: Indirect Land Use Change; IMO: International Maritime Organisation; LBM: Liquefied Biomethane; LCA: Life Cycle Assessment; LNG: Liquefied Natural Gas; LPG: Liquefied Petroleum Gas; MCDM: Multiple Criteria Decision Making; MDO: Marine Diesel Oil; MGO: Marine Gas Oil; NOAA: National Oceanic and Atmospheric Administration; NOX: Nitrogen Oxides; PM: Particulate Matter; SOX: Sulphur Oxides; SVO: Straight Vegetable Oil; TRL: Technological Readiness Level; TTW: Tank-to-wake; UCO: Used Cooking Oil; ULSFO: Ultra-Low Sulphur Fuel Oil; UNCTAD: United Nations Conference on Trade and Development; VLSFO: Very Low Sulphur Fuel Oil; WTT: Well-to-tank; WTW: Well-to-wake
Keywords: Biofuel; optimum biofuel; sustainable biofuel; life cycle assessment; ILUC; Maritime transportation; MICROALGAE; Engineering